DAMPAK PEMBERIAN TAMBAHAN PENGHASILAN PADA KINERJA PEGAWAI NEGERI SIPIL: ( STUDI PADA KANTOR CAMAT NGEBEL KABUPATEN PONOROGO ) - Windari Windari (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The purpose of the study to find out and analyze the impact of the provision ofAdditional Income on the performance of Civil Servants in the Office of The DistrictHead of Ngebel Ponorogo.Qualitative descriptive research type. Research objectsare based on people's data sources, documents and events.Selection of informantswith purposive sampling techniques. Interview, observation and documentationdata collection techniques. Data instruments in the form of a list of questions,observations and recordings. Data analysis techniques using interactive dataanalysis of miles &huberman models. The impact was analyzed with Finsterbuschtheory and Motz Single before-after program according to and performance theoryaccording to John Miner with indicators of quality, quantity, use of time in workand cooperation.The results showed that the implementation of AEI was going wellbut there were still technical constraints.Quality there is an improvement in thequality of the work and a decrease in the error rate although not too great.Thepositive impact on the quantity of budget realization efficiency and realization oforganizational performance achievement exceeds the target above 100%.The useof time in work there is a decrease in violations of working hours at the rate ofabsence, the rate of delay and quick return.The effective working time of employeesin 2020 averaged 85%. While in the aspect of cooperation is not seen the impactbecause it has been running well before the AEI.Keywords : Impact, Additional Employee Income, Performance